MAN POWER REDUCTION EFFECT ON RAIL BRIDGE FABRICATION - van Hoten, Hendri; Nurbaiti, Nurbaiti (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
The research is to analysis the effect of reducing manpower for production process railroad bridge WTT46.5 type. The purposed manpower reduction is to increased effective production process railroad bridge WTT46.5 type and reduction manpower cost. Reduction of Manpower happened in trial process with the number 15 people and separated in some part. On of the part is in welder that is reduction in one person. Manpower reduction in trial process to improve company finance by Rp.  4.645.620,00 in every project.